Analysis of rain fade duration over satellite-earth path at Ku-Band in tropics - Dao, Hassan; Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed; Ismail, Ahmad Fadzil (2012)
Statistical analysis is fundamental information for system engineer to design and plan satellite communication link. Fade duration is one aspect of fade dynamics that contributes designing of fade mitigation techniques (FMT). This paper presents statistical analysis on fade duration on high elevation angle (77.4°) in Ku-band carried out in Kuala Lumpur, Malaysia with 12 months duration statistics.